Metode Pembenihan Ikan koi Cyprinus carpio dalam menghasilkan benih berkualitas di Mizumi Koi Farm, Kabupaten Sukabumi, Jawa Barat. - Andri Hendriana; Fajar Ridwansyah; Andri Iskandar; Asep Syamsul Munawar; Deni Lugina (Jurnal Perikanan Terapan, 2021)
Koi fish is one of the ornamental fish commodities which is popularly cultivated in Indonesia. This fish has an attraction because of its very beautiful color and is often used as a contest fish. Every year the demand for koi fish continues to increase both in domestic and foreign markets so that it have promising business prospects. One of the prospects is in hatchery activities which include container preparation activities, broodstock maintenance, broodstock spawning, egg hatching, larval rearing, seed maintenance, denial maintenance, water quality management, pest and disease prevention, and harvesting. One of the koi fish hatcheries is Mizumi Farm, located in Sukabumi, West Java. The productivity of koi fish in that location includes the number of eggs produced around 116,452 eggs, 81% fertilization rate (FR), 75% hatching rate (HR), 63% larval survival rate (SR), 63% SR of seed / white matter and SR of denial. 74%. The results showed a total of fish is 634 tail with a size of 5 cm. Marketing of koi fish seeds at Mizumi Farm includes fostered partners, hobbyists in the Sukabumi area and other cities.